Association between Sleep Problems and Psychopathologies among Preschoolers: A Brazilian Cross-Sectional Study - Renatha El Rafihi-Ferreira; Felipe Alckmin-Carvalho; Marina Monzani da Rocha; Thiago Soares Campoli; Thomas Hubert Ollendick (Sleep Science)
Objective To evaluate the relationship between sleep problems and psychopathologies in Brazilian preschool children.